Situation Report: Romania, 1 March 1960 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Coordination of City, Town Planning More on Agriculture in the Bucharest Region Change in Geology Committee May Reflect Dissatisfaction over Oil Production "Die Presse" Report of Romanian Protest to Hungary Comment on Living Standards